Manajemen Kurikulum Satuan Pendidikan Kerja Sama sebagai Upaya Peningkatan Pendidikan Perspektif Global (Studi Kasus SD Sampoerna Bumi Serpong Damai Tangerang Selatan) - Curry Wulanningrum; Hasyim Asy’ari; Zahruddin Zahruddin (Mathematics Education Study Program, 2025)
This study aims to examine curriculum management in Satuan Pendidikan Kerja Sama (SPK) as an effort to enhance global perspective education, focusing on a case study at Sampoerna Elementary School, Bumi Serpong Damai. This research employs a qualitative approach with a case study method to describe the planning, implementation, and evaluation processes of the applied curriculum and to analyze the supporting and inhibiting factors in its application. The findings reveal that Sampoerna Elementary School adopts the Cambridge curriculum integrated with the national curriculum, providing a balance between global awareness and Indonesian cultural values. However, several challenges were identified, such as overlaps between the two curricula and a lack of comprehensive understanding among stakeholders regarding the SPK concept. The strategies implemented include technology-based learning, the integration of 21st-century soft skills, and collaboration with international institutions.